2020
DOI: 10.1080/1034912x.2020.1746246
|View full text |Cite
|
Sign up to set email alerts
|

Friendship Experiences of Young Adults Who Use Augmentative and Alternative Communication

Abstract: Researchers Links Grants #98089). Opinions expressed and conclusions arrived at are those of the author and are not necessarily the funders.The authors would like to thank all the persons who use AAC and their carers who served as participants in the study for their time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Whereas learning to read and write is universally important, it is presumably even more crucial for students having difficulties with speech. Their challenges with natural speech necessitate the use of AAC (Dada, Tonsing, & Goldbart, 2020), and the technological progress regarding AAC has increased their ability to participate in social settings and to be part of various activities. This is important because research has shown that activity and participation restrictions affect literacy development more than the severity of disabilities among students who use ACC .…”
Section: Earlier Researchmentioning
confidence: 99%
“…Whereas learning to read and write is universally important, it is presumably even more crucial for students having difficulties with speech. Their challenges with natural speech necessitate the use of AAC (Dada, Tonsing, & Goldbart, 2020), and the technological progress regarding AAC has increased their ability to participate in social settings and to be part of various activities. This is important because research has shown that activity and participation restrictions affect literacy development more than the severity of disabilities among students who use ACC .…”
Section: Earlier Researchmentioning
confidence: 99%